Antecedents and consequences of luxury brand engagement in social media. Issue 2 (9th September 2019) - Brandão, Amélia; Pinho, Eva; Rodrigues, Paula
Abstract : Purpose: The purpose of this study is to analyse the antecedent (Consumer Involvement) and the consequences (Brand Connection and Brand Usage Intent [BUI]) of the three dimensions of Consumer Brand Engagement (CBE) (Cognitive Processing, Affection and Activation) in luxury brand engagement on Facebook. Design/methodology/approach: Data were collected through an online questionnaire completed by fans/followers of luxury brands' Facebook pages. The empirical study was conducted using structural equation modelling. Findings: Consumer Involvement has a positive impact on the three dimensions of CBE (Cognitive Processing, Affection and Activation). This leads to the conclusion that Activation and Affection have an impact both on Self-Brand Connection and on BUI. Moreover, it was found that Cognitive Processing impacts only on BUI. Practical implications: The results identified the factors which brand managers should focus on to increase CBE on Facebook. Originality/value: This study is a pioneer, as it extends the consumer engagement model to the social media context in a hedonic and conspicuous consumption category which includes luxury brand products. Abstract : Propósito: Esta investigación analiza el antecedente (compromiso del consumidor) y las consecuencias (conexión con la marca e intención de uso de marca) de las tres dimensiones del compromiso del consumidor con la marca (procesamiento cognitivo, afectivo y activo) en el compromiso con la marca de lujo en Facebook. Diseño/metodología/enfoque: Los datos se obtuvieron a través de un cuestionario online de los seguidores de varias páginas de marcas de lujo en Facebook. El estudio empírico se realizó utilizando un modelo SEM. Hallazgos: El compromiso del consumidor tiene un impacto positivo en las tres dimensiones del compromiso del consumidor con la marca (procesamiento cognitivo, afectivo y activo). Esto lleva a concluir que los procesos activo y afectivo tienen un impacto tanto en la conexión con la marca como en su intención de uso. Además, se constató que el proceso cognitivo sólo afecta a la intención de uso de la marca. Implicaciones prácticas: Los resultados identificaron los factores en los que los directores de marca deberían centrarse para aumentar el compromiso del consumidor hacia la marca en Facebook. Originalidad/valor: Este estudio es pionero, dado que extiende el modelo de compromiso del consumidor al contexto de las redes sociales en una categoría de consumo hedónico y ostentoso que incluye a bienes y servicios como las marcas de lujo.